2021
DOI: 10.3390/antibiotics10040387
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Structure Harboring blaCTX-M-27 on IncF Plasmids in Escherichia coli Isolated from Swine in China

Abstract: The aim of this study was to elucidate the prevalence of blaCTX-M-27-producing Escherichia coli and transmission mechanisms of blaCTX-M-27 from swine farms in China. A total of 333 E. coli isolates were collected from two farms from 2013 to 2016. Thirty-two CTX-M-27-positive E. coli were obtained, and all were multidrug-resistant. Pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) profiles indicated a wide range of strain types that carried blaCTX-M-27, and the sequence type ST10 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…It reveals that there is diversity in ST types in Hubei province. In some other surveys, ST101 (7/53, 13.21%) [22] and ST101 (3/32, 9.4%) [14] were common STs, these are similar to our result ST101 (3/29, 10.3%). In Yang′s study, the common ST was ST10 (22/171, 12.9%), followed by ST744 (8/171, 4.7%), ST101 (7/171, 4.1%), ST165 (5/171, 2.9%) [17] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It reveals that there is diversity in ST types in Hubei province. In some other surveys, ST101 (7/53, 13.21%) [22] and ST101 (3/32, 9.4%) [14] were common STs, these are similar to our result ST101 (3/29, 10.3%). In Yang′s study, the common ST was ST10 (22/171, 12.9%), followed by ST744 (8/171, 4.7%), ST101 (7/171, 4.1%), ST165 (5/171, 2.9%) [17] .…”
Section: Discussionsupporting
confidence: 93%
“…Recently, E. coli ST10 has not only been presented by animals in China but also raised the ST10 from human infections in China [23] . Zhang et al showed that the most prevalent ST was ST10 (16/32, 50%) [14] . However, ST10 (2/29, 6.9 %) of the result in this study seem to con ict with those from most previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Studies investigating the role of certain veterinary drugs in the emergence of particular ESBL enzymes are lacking. Ceftazidime use is prohibited in food production animals, 48 but the gene encoding CTX-M-27 has been reported in E. coli isolated from swine, 49,50 beef cattle, 50 and poultry. 51 In this study, food containing all of these major proteins also had E. coli with a bla CTX-M-27 gene present.…”
Section: Discussionmentioning
confidence: 99%